De novo small deletion affecting transcription start site of short isoform of AUTS2 gene in a patient with syndromic neurodevelopmental defects. Issue 3 (21st December 2020) - Martinez‐Delgado, Beatriz; Lopez‐Martin, Estrella; Lara‐Herguedas, Julián; Monzon, Sara; Cuesta, Isabel; Juliá, Miguel; Aquino, Virginia; Rodriguez‐Martin, Carlos; Damian, Alejandra; Gonzalo, Irene; Gomez‐Mariano, Gema; Baladron, Beatriz; et al.
Abstract: Disruption of the autism susceptibility candidate 2 (AUTS2) gene through genomic rearrangements, copy number variations (CNVs), and intragenic deletions and mutations, has been recurrently involved in syndromic forms of developmental delay and intellectual disability, known as AUTS2 syndrome. The AUTS2 gene plays an important role in regulation of neuronal migration, and when altered, associates with a variable phenotype from severely to mildly affected patients. The more severe phenotypes significantly correlate with the presence of defects affecting the C‐terminus part of the gene. This article reports a new patient with a syndromic neurodevelopmental disorder, who presents a deletion of 30 nucleotides in the exon 9 of the AUTS2 gene. Importantly, this deletion includes the transcription start site for the AUTS2 short transcript isoform, which has an important role in brain development. Gene expression analysis of AUTS2 full‐length and short isoforms revealed that the deletion found in this patient causes a remarkable reduction in the expression level, not only of the short isoform, but also of the full AUTS2 transcripts. This report adds more evidence for the role of mutated AUTS2 short transcripts in the development of a severe phenotype in the AUTS2 syndrome.